2017
DOI: 10.3892/etm.2017.4088
|View full text |Cite
|
Sign up to set email alerts
|

The traditional Korean herbal medicine Ga-Gam-Nai-Go-Hyan suppresses testosterone-induced benign prostatic hyperplasia by regulating inflammatory responses and apoptosis

Abstract: Benign prostatic hyperplasia (BPH) is a pathological condition that affects the majority of men above the age of 50 years. Pharmacological agents are typically used to treat BPH; however, there are currently no pharmacological agents that are able to completely cure BPH without causing adverse side effects. As a result of these side effects, there is a great interest in developing effective herbal medicines that are able to inhibit the progression of BPH and are safe for long-term use. Ga-Gam-Nai-Go-Hyan (GGN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…The development of BPH is closely associated with dysregulation of androgens, increased proliferation and decreased apoptosis of cells in the prostate. This is approved in our study that showed significant decrease of apoptotic marker (caspase3) in group III and this finding is supported by previous studies . Group IV showed highly over expressed caspase3 explaining marked apoptotic features, damage and death of prostatic tissue.…”
Section: Discussionsupporting
confidence: 92%
“…The development of BPH is closely associated with dysregulation of androgens, increased proliferation and decreased apoptosis of cells in the prostate. This is approved in our study that showed significant decrease of apoptotic marker (caspase3) in group III and this finding is supported by previous studies . Group IV showed highly over expressed caspase3 explaining marked apoptotic features, damage and death of prostatic tissue.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, disruptions and thickening of the basement membrane were observed. These histopathological changes induced by TP align with previous studies [ 41 , 42 ] and were alleviated by TH, as evidenced by significantly lower histological scores and epithelial thickness compared to the control group. Alongside the decreased prostate weight, these histopathological results suggest that TH possesses an inhibitory effect on benign prostatic hyperplasia.…”
Section: Discussionsupporting
confidence: 90%
“…Recent research suggests that herbs used in oriental medicine can effectively treat BPH or inhibit the occurrence of BPH [ 13 , 14 , 15 ]. These herbal extracts contain alkaloids, flavonoids, isoflavones, saponins, and other phenolics.…”
Section: Introductionmentioning
confidence: 99%